2016
DOI: 10.3390/app7010024
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Characterization of Immobilized TiO2/PEG by Using DSAT as a Support Binder

Abstract: Immobilized TiO 2 was prepared by adding a small composition of polyethylene glycol (PEG) as a binder, and this paper reported for the very first time the formation of C=O from oxidized PEG, which acted as an electron injector in enhancing photoactivity. Water-based TiO 2 with PEG formulation was deposited by using a brush technique onto double-sided adhesive tape (DSAT) as a support binder to increase the adhesiveness of immobilized TiO 2 . The photocatalytic activity of immobilized TiO 2 -PEG was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 53 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…The diffraction pattern does not show any anatase phase because of the annealing temperature factor whereby the anatase phase of TiO 2 will slowly form from the brookite phase of the TiO 2 when the annealing temperature increases to 500–600 °C [ 19 ]. The previous work done by Fischer et al (2017) stated that the anatase phase of TiO 2 would grow better at a higher temperature [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction pattern does not show any anatase phase because of the annealing temperature factor whereby the anatase phase of TiO 2 will slowly form from the brookite phase of the TiO 2 when the annealing temperature increases to 500–600 °C [ 19 ]. The previous work done by Fischer et al (2017) stated that the anatase phase of TiO 2 would grow better at a higher temperature [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Under identical conditions, it was found that only 18.7% of MB dye solution was adsorbed on the immobilized TiO2 in the dark after 30 min, while the amount of MB removed by the TiO2/PEG was 47.4% [26]. This suggests that the greater adsorption of MB on TiO2/PEG as compared to immobilized TiO2 is attributed to the higher surface area of TiO2/PEG (Brunauer-Emmett-Teller (BET) surface area of the photocatalysts: TiO2/PEG, 88 m 2 /g; TiO2, 49 m 2 /g).…”
Section: Photoactivity Tests Of Immobilized Tio2 and Tio2/peg Under Dmentioning
confidence: 99%
“…The MB dye was used as a target pollutant in aqueous media to assess the photocatalytic activity. This study serves as an extension of our immobilization reports [26]; thus, the influence of experimental parameters such as aeration flow rate, initial dye concentration, and effect of pH were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Dye-sensitized solar cell (DSSC) discovered by Grätzel [7] has emerged the potential of TiO2 as important element in early stage of PV. In the contrary, the photoactivity of TiO2 is restricted to ultraviolet (UV) region because of the wide band gap energy [8][9][10][11][12][13][14]. To overcome the band gap issue, researchers made attempts to broaden the optical response of TiO2 to visible light by surface modification, doping with metal or non-metal, dye or semiconductor sensitization [15][16][17].…”
Section: Introductionmentioning
confidence: 99%